Pedagogical Innovation in Higher Education is an Important Factor of Improving the Quality of Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the priorities of the radical reform of the higher education system of Uzbekistan in the years of independence, the fact that the socio-economic development of our country depends primarily on the training of well-educated, mature specialists, and the improvement of the quality of the education system The theoretical basis of the current state and development of innovative activity is explained, it describes the essence of improving the quality of the educational system, the theoretical basis of the organization of innovative activity, and the current state and development of the effective use of information and communication technology opportunities in the educational process in the field of information and communication technologies.